Efficacy and tolerability of racecadotril in the treatment of cholera in adults: a double blind, randomised, controlled clinical trial. Issue 10 (11th September 2003) - Alam, N H; Ashraf, H; Khan, W A; Karim, M M; Fuchs, G J
Abstract : Background: The enkephalins, endogenous opiate substances, act as neurotransmitters along the entire digestive tract where they elicit intestinal antisecretory activity without affecting intestinal transit time or motility. Racecadotril, through inhibition of enkephalinase, reinforces the physiological activity of endogenous enkephalins and, therefore, shows intestinal antisecretory activity. Aim: We conducted the study to determine the role of racecadotril as an adjunct to the standard treatment of cholera in adults. Methods: The study was a double blind, randomised, placebo controlled clinical trial involving 110 adult male cholera patients who received either racecadotril or placebo in addition to standard cholera treatment. The major outcome measures (stool output, oral rehydration solution (ORS) intake, requirements for unscheduled intravenous fluid infusion, and duration of diarrhoea) were compared between the groups. Results: Of 110 patients enrolled, 54 received racecadotril and 56 received placebo. Admission clinical characteristics were comparable between the groups. There was no significant difference in (mean (SD)) total stool output (racecadotril v placebo 315 (228) v 280 (156) g/kg), total ORS intake (390 (264) v 369 (240) ml/kg), or duration of diarrhoea (35 (15) v 32 (13) hours) between the groups. Clinical success, defined as resolution of diarrhoea within 72 hours of initiation of study intervention, was similar in both groups (racecadotril v placebo 96% v 89%). The number of patients receiving unscheduled intravenous infusions was not significantly different between the groups (racecadotril v placebo 22% v 14%). No drug related adverse effect was noted. Conclusion: The study demonstrated that racecadotril therapy, although found to be safe, does not provide additional benefit in the treatment of severe cholera in adults.